2016
DOI: 10.1177/0021955x16681450
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility, morphology and mechanical properties of polylactic acid/polyolefin elastomer foams

Abstract: In this study, different blends based on polylactic acid (PLA)/polyolefin elastomer (POE) and compatibilized PLA/POE was prepared by melt mixing. The compatibilizer glycidyl methacrylate-grafted-polyolefin elastomer (POE-g-GMA) was synthesized in a separate process. The Fourier transform infrared spectrum confirmed the reaction of POE and glycidyl methacrylate. Meanwhile, the morphology of dispersed phase was observed by scanning electron microscope. The results indicated that the compatibilizer has improved t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…When the up to 5 wt% content of POE increase in the PLA matrix, the crystallinity of PLA reduces, and decreasing the crystallinity is accompanied by reducing in tensile strength [11]. Similar results in the case of tensile strength of PLA/POE blends were also achieved by Forghani et al [46]. With respect to different parts of the Figure 5, it is demonstrated that the highest value of tensile strength was obtained by the addition of 2 wt% content of carbon black into the PLA matrix by 67 MPa.…”
Section: Mechanical Properties 331 Tensile Strengthsupporting
confidence: 79%
See 1 more Smart Citation
“…When the up to 5 wt% content of POE increase in the PLA matrix, the crystallinity of PLA reduces, and decreasing the crystallinity is accompanied by reducing in tensile strength [11]. Similar results in the case of tensile strength of PLA/POE blends were also achieved by Forghani et al [46]. With respect to different parts of the Figure 5, it is demonstrated that the highest value of tensile strength was obtained by the addition of 2 wt% content of carbon black into the PLA matrix by 67 MPa.…”
Section: Mechanical Properties 331 Tensile Strengthsupporting
confidence: 79%
“…Figure 7b indicates that Young's modulus of the PLA matrix was dramatically raised by increasing carbon black content up to 2 wt% from 300 to 506 MPa. Young's modulus of PLA improves with adding carbon black concentration since these spherical nanoparticles are stiffer than polymer matrix [46]. Liu et al [45] reported that the addition of carbon black nanoparticles up to 5 wt% into the PLA matrix had increased its Young's modulus properly.…”
Section: Young's Modulusmentioning
confidence: 99%
“…Glycidyl methacrylate (GMA) grafted polyolefin elastomers (POE) are often used in polyester blends (Hu et al, 1996;Forghani et al, 2018). Consequently, as PLA shows a good chemical functionality (Sun et al, 2011) it can be combined with POE-g-GMA.…”
Section: Introductionmentioning
confidence: 99%
“…18 There are many studies in the oxo-material degradability properties. 19,20 Environmental conditions such as humidity and the presence of oxygen can result in a very different biodegradability of the polyethylene. [16] Forty-eight percent biodegradability was measured for the polyethylene including oxo-material after 90 days.…”
Section: Introductionmentioning
confidence: 99%
“…It is comparatively brittle, and therefore, it can be used as an additive to make the degradability of polyethylene higher. 19,20 Environmental conditions such as humidity and the presence of oxygen can result in a very different biodegradability of the polyethylene. It has been shown that the temperature is also an important fact to accelerate the degradation of the polymers in the nature.…”
Section: Introductionmentioning
confidence: 99%